GENDER INEQUALITY IN WOMEN'S ACCESS TO ENVIRONMENTAL RESOURCES - Ariyani, Linda; Wardina, Miza; Herawati, Leni; Aggraini, Dinda Putri; Mukti, Ichrar Syahbani (Communale Journal, 2023)
Gender inequality is an issue that has long been debated in various fields, including women's access to environmental resources. This research was conducted by conducting a literature review of articles, journals, and other relevant publications. The literature review method was used to collect and analyze information from previous researchers on Gender Inequality in Women's Access and Environmental Resources. Based on some of these research references, it can be concluded that gender inequality in women's access to environmental resources is a real issue in various contexts. Measures to improve gender equality in access to environmental resources include strengthening the role of women in decision-making, social change, and inclusive policies and a gender-based approach in environmental program planning and implementation. Collective efforts from the government, civil society, and the private sector are needed to overcome gender inequality and achieve sustainable development that is just and sustainable.